Approximate Conformal Mappings and Elasticity Theory. (28th August 2016) - Ivanshin, Pyotr N.; Shirokova, Elena A.
Abstract : Here, we present the new method of approximate conformal mapping of the unit disk to a one-connected domain with smooth boundary without auxiliary constructions and iterations. The mapping function is a Taylor polynomial. The method is applicable to elasticity problems solution.